Síntese e caracterização de nanopartículas de Nb2O5 e estudo de suas propriedades fotocatalíticas - Lopes, Osmando Ferreira (Universidade Federal de São Carlos, 2013)
In this study, the use of niobium oxide nanoparticles (Nb2O5) prepared through the OPM method as photocatalysts for the degradation of pollutants was investigated, describing the dependence on hydrothermal parameters (temperature and time) in aspects such as morphology, structure, electronic properties, and how these factors influence the photocatalytic activity. The catalytic activity of the samples was probed by evaluating the photodegradation under UV and visible irradiation of a dye (Rhodamine B, Rod.B) and a pesticide, Atrazine. An indirect measurement of the hydroxil radicals produced in the catalyst s surface was done by fluorescence spectroscopy, in order to evaluate the importance of this mechanism in the degradation process. The results showed that the Nb2O5 nanoparticles prepared by the OPM method are promising for the catalysis of photoactivated reactions. Surface hydroxylation and crystallinity were shown as the most important parameters involved in the activity per area of the nanoparticles, where the surface hydroxylation was more influent in the samples obtained in low temperature, whereas crystallinity was the key parameter for the obtained in higher temperatures. Under ultraviolet irradiation, the main photodegradation mechanism was governed by the . OH radical generation and attack. On the other hand, the dye-sensitization mechanism was shown as the main path for the degradation of Rod.B under visible irradiation.
Synthesis and characterization of Nb2O5 nanoparticles and study of their photocatalytic properties
Keywords: Fotocatálise; Óxido de nióbio; Nanopartículas; Descontaminação de águas; CIENCIAS EXATAS E DA TERRA::QUIMICA